Women's Activism in Malaysia Voices and Insights - Lee, Julian C. H. (Springer International Publishing, 2018)
In this book, the author draws on over a decade of first-hand experience as an academic-activist and on interviews with women in Malaysia's women's rights movement. Despite a considerable array of challenges to their participation in the public and political spheres, the movement is especially vibrant. Presenting insights from feminist activists in Malaysia, the book explores the Women's Candidacy Initiative's efforts to promote independent women in Parliament; the work of women's coalition the Joint Action Group for Gender Equality; how activists understand and experience the concept of feminism; and finally the place of men in feminism. Women's Activism in Malaysia will be of interest to students and scholars across a range of disciplines including gender studies, politics and sociology. .